2020
DOI: 10.1186/s43019-020-00061-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of posteromedial corner injuries on clinical outcome and second-look arthroscopic findings after allograft transtibial anterior cruciate ligament reconstruction

Abstract: Background The purpose of this study was to evaluate the influence of posterior medial corner (PMC) injuries on clinical outcome and second-look arthroscopic findings after anterior cruciate ligament (ACL) reconstruction. Methods Seventy-eight consecutive patients underwent a second-look arthroscopic surgery after ACL reconstruction and magnetic resonance imaging (MRI) examination of the PMC. The patients were divided into a PMC intact group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Basically, higher engagement in physical and sports activities will lead to a higher chance of ACL injury. 7) It can be presumed that the number of people engaging in high-level athletics is higher in Western countries than in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, higher engagement in physical and sports activities will lead to a higher chance of ACL injury. 7) It can be presumed that the number of people engaging in high-level athletics is higher in Western countries than in Korea.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 20 However, the clinical outcomes of MM repair were known to be less successful than those of LM repair. 21 , 54 Kim et al 21 reported that the healing rate was 80% with MM repair but 91.2% with LM repair. Recent systemic review studies reported that the overall healing rate ranged from 75.6% to 76.1% with MM repair but 80.5% to 87.4% with LM repair.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 5 , 6 , 14 , 31 , 48 , 53 However, observation of failed healing after meniscal repair indicated that findings using an MRI scan may not entirely correlate with clinical failures or findings of second-look arthroscopy. 40 , 51 , 53 , 54 Several studies have noted that some incomplete or unhealed meniscal lesions identified on MRI scans were found to be completely healed at the time of second-look arthroscopy and healed clinically. 31 , 41 These MRI findings of incomplete or unhealed meniscal lesions could be found for many years after successful meniscal repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCL is one of the major ligaments supporting the knee joint and is the most commonly injured ligament [1,66,67]. Considering the neglected injuries and the recent increasing popularity of sports participation among both the general public and professional athletes, the frequency of MCL injuries might be much higher than expected.…”
Section: Summary and Future Directionmentioning
confidence: 99%